INSURANCE LITERACY AS A CATALYST FOR COMMUNITY EMPOWERMENT AND FINANCIAL INCLUSION - Nurhayati; Wijaya, Richy; Esya, Lavlimatria; Wijayanto, Rakendro; Laksmi Subadra, Ni Putu Ayu (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The Community Service Program (PkM) by Trisakti University, titled